Factors associated with a positive cytological result in Papanicolau tests in women attended In the Peruvian league against - Venegas, Gino (2021)
Objetive: To evaluate the factors associated with a positive cervical cytology result in the Pap smear test in a sample of Peruvian women from Lima, Peru - 2013. Material and Methods: We conducted an analytical cross-sectional study including women from 21 to 64 years and we used the Pap smear test to evaluate cervical cytology. We included sociodemographic and medical history variables obtained from medical records of the patients. We elaborated generalized linear models from Poisson family with robust variances to evaluate the factors associated with positive cytology. The association measure reported was the prevalence ratio (PR) with their respective 95% confidence intervals (95%CI). Results: We analyzed 11110 women with a mean age of 41.5 ± 10.9 years and a prevalence of a positive Pap smear test of 2.8%. In the adjusted model, we found that women between 21 and 30 years old (aPR=1.97; 95%CI:1.30-3.00), 31 to 40 years (aPR=2.56; 95%CI:1.76 -3.72) and 41 to 50 years (aPR=2.16; 95%CI:1.47-3.17), single (aPR=1.41; 95%CI:1.10-1.83), widowed or divorced (aPR=1.90; 95%CI:1.27-2.87), with a sexual life onset before 16 years (aPR=1.30; 95%CI:1.01- 1.68) or between 16 and 19 years (aPR=1.69; 95%CI:1.22-2.36) had a greater prevalence of a positive cervical cytology result. Conclusions: Cervical cancer is a public health problem in Peru, then, identifying the factors associated will allow us to improve screening strategies and prioritize groups at higher risk.